Frost resistance of fiber-reinforced blended slag and Class F fly ash-based geopolymer concrete under the coupling effect of freeze-thaw cycling and axial compressive loading. (30th July 2020) - Yuan, Yuan; Zhao, Renda; Li, Rui; Wang, Yongbao; Cheng, Zhengqing; Li, Fuhai; John Ma, Zhongguo
Highlights: Three types of fiber were added to enhance the compressive strength and frost resistance. The coupling effect of freeze-thaw cycling and axial compressive loading was studied. S fiber has a complicated impact on the structural compactness and frost resistance of FGPC under pressure. Abstract: The poor frost resistance of low-calcium geopolymer concrete is an urgent problem that needs to be solved before its application in practice. In this study, polypropylene (PP) fiber, polyvinyl alcohol (PVA) fiber and steel (S) fiber were added to enhance the frost resistance of blended slag and Class F fly ash-based geopolymer concrete (SFGPC). More importantly, to evaluate the frost resistance of fiber-reinforced SFGPC under axial compressive loading, a coupling experiment with 20 MPa of compressive stress and 125 freeze-cycles was conducted. It was found that the addition of fibers did not inhibit the initiation of microcracks but could suppress their propagation. The water penetration depth and mercury intrusion porosimetry (MIP) test results verified that the applied compressive loading further compacts the concrete, which significantly improves the frost resistance. In comparison, the S fiber-reinforced SFGPC exhibited an inconsistent frost resistance with and without compressive stress due to the extremely high elastic modulus of the S fiber. Overall, 0.3% vol PVA fiber had the best effect on improving both the mechanical properties and the frost resistance of SFGPC.